Regulation by Contract : A New Way to Privatize Electricity Distribution? - Bakovic, Tonci; Tenenbaum, Bernard; Woolf, Fiona (Washington, DC: World Bank, 2013)
In with the performance of recently privatized electricity distribution companies. Governments complain that tariffs have increased without visible improvements in service. Investors contend that they have not earned reasonable returns on their investments. Both sides often express dissatisfaction with the new independent regulatory commissions established at the time of privatization. In particular, investors argue that the commissions have not lived up to their commitments and almost always side with consumer interests. Some investors claim that the design of the new regulatory system in many developing and transition economies is fundamentally flawed. They often recommend that independent regulatory commissions be supplemented or replaced by more explicit "regulation by contract." This paper examines whether regulation by contract or a combination of regulation by contract and regulatory independence would provide a better regulatory system for developing countries that wish to privatize some or all of their distribution systems. The paper: Describes the key characteristics of regulation by contract as it has been implemented in several developing countries Focuses on how regulatory contracts in several countries handle certain key issues (pass-through of power-purchase costs, foreign exchange fluctuations, loss reduction and the obligation to serve) Describes the strengths and weaknesses of different approaches for dealing with disputes that inevitably arise in the application of regulatory contracts Compares and contrasts some recent experiences of distribution entities in Latin America and India. Examines some of Brazil's recent problems that may have arisen because Brazil adopted a flawed variant of regulation by contract. The paper concludes with a discussion of some lessons that can be learned from the experience of several countries.